Innovative Delivery Models for Iron Beans Resulted in Adoption by an Estimated 442,000 Households in Rwanda - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Since 2010, HarvestPlus, the Rwanda Agricultural Board (RAB), and CIAT have managed a successful iron bean delivery program in Rwanda. By the end of 2018, around 442,000 households were growing iron beans, with 15% of the population consuming them. Innovative seed certification facilitated quality seed production, while direct marketing and payback delivery models increased rapid adoption and reduced disadoption, respectively. In 2019, HarvestPlus co-established with RAB a platform to further scale delivery and handed over the program to RAB.